Design of a Rushton Turbine for the Improvement of the Bioreactor in the Wastewater Treatment Plant in the City of Morococha (Carhuacoto)-Peru - Condor Jaucha, Frando (2023)
The study is carried out in a domestic wastewater treatment plant (DWWTP) in the city of Morococha in Peru, with a population of 9 thousand inhabitants, at an altitude of 4200 m.a.s.l., has a processing capacity of 1620 m3 /day with a flow that is not constant, focuses on secondary treatment consisting of a sequential biological reactor (SBR) of aerobic technology. The problem is the excess flow in certain periods of time and the incoming wastewater was not processed in an optimal way, as an objective a redesign of the bioreactor was proposed, incorporating a Rushton Turbine of 6 horsepower (H.P.) of power with 6 propellers and dimensioned according to mathematical models, the results were the improvement of effluent quality for turbidity, dissolved oxygen, pH and re- sidual chlorine, improving the reaction speed, and controlling the treatment flow, providing a better quality effluent to the receiving body which is a nearby river in this way the negative environmental impacts are reduced for the population.